1959
DOI: 10.2134/agronj1959.00021962005100020016x
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Protein Content of Irrigated Napiergrass, Guineagrass and Pangolagrass as Affected by Nitrogen Fertilization1

Abstract: Synopsis Irrigated, properly fertilized napiergrass, guineagrass and pangolagrass produced 51,491, 41,714, and 18,907 pounds of dry forage per acre yearly, respectively. Yields of napiergrass and guineagrass increased markedly with nitrogen rates up to 800 pounds of N per acre yearly. Protein content of all the grasses increased with nitrogen fertilization up to the 1,600 pound level at which it approached 12% with all species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
3

Year Published

1962
1962
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 0 publications
3
12
3
Order By: Relevance
“…. The relative N uptake for the vanous treat.ments IS similar to other reports (I, 18,24,26,30)-~angmg fro.m 26 to 55% in 1980 and from 17 to 70% m 1981 (Fig. 2).…”
Section: Methodssupporting
confidence: 89%
“…. The relative N uptake for the vanous treat.ments IS similar to other reports (I, 18,24,26,30)-~angmg fro.m 26 to 55% in 1980 and from 17 to 70% m 1981 (Fig. 2).…”
Section: Methodssupporting
confidence: 89%
“…range from 2.0 to 2.6 g kg −1 , while a range of 2.4 to 2.8 g P kg −1 is suggested as the critical P level for common and 'Midland' bermudagrass (Adams et al, 1967). Little et al (1959) reported critical tissue P concentrations of 1.2 to 1.6 for 'Pangola' grass (Digitaria eriantha Steud. ).…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to select model parameters so as to minimize E. By this criterion, the 3rd order polynomial would be the preferred model because it provides perfect fit of the data (within round off error). Little et al [10] measured yield response of Napiergrass (Pennisetum purpureum), Guineagrass (Panicum maximum), and Pangolagrass (Digitaria decumbens) at applied N up to 1800 kg ha 21 in Puerto Rico and also found no evidence of a downturn in response. 1, this model exhibits weird behavior outside the data points, which is not expected on physical grounds.…”
Section: Discussionmentioning
confidence: 99%
“…(10) and (11), respectively. Next there is the practical matter of how to evaluate the coefficients for the model.…”
Section: Discussionmentioning
confidence: 99%